2004
DOI: 10.1002/bjs.4543
|View full text |Cite
|
Sign up to set email alerts
|

Functional and physiological outcome following transanal repair of rectocele

Abstract: Transanal repair of rectocele is a safe alternative to posterior colporrhaphy. It provides improvement in symptoms, reflected by anatomical improvement with minimal complications and no increase in dyspareunia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 24 publications
2
26
1
Order By: Relevance
“…However, transanal repair may compromise anal sphincter pressure, although it is not considered to cause severe fecal incontinence postoperatively [11, 25, 26]. Other studies have not demonstrated any significant reduction of anal sphincter pressure [2, 11, 13, 16, 19], although a few have noted a reduction of threshold volume and/or rectal compliance [2, 11]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, transanal repair may compromise anal sphincter pressure, although it is not considered to cause severe fecal incontinence postoperatively [11, 25, 26]. Other studies have not demonstrated any significant reduction of anal sphincter pressure [2, 11, 13, 16, 19], although a few have noted a reduction of threshold volume and/or rectal compliance [2, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of these physiologic investigations would be certainly advisable for comprehensive assessment of anorectal functional disorders. It is generally accepted that surgery for rectocele does not affect anal sphincter function as measured by manometry [1,2,3, 11, 12], though van Dam et al [26] reported a risk of impaired fecal continence after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations